The AR glasses’ “non-neutrality”: their knock-on effects on the subject and on the giveness of the object - Liberati, Nicola; Nagataki, Shoji (Ethics and information technology, 2015)
This work focuses on augmented reality glasses and its aim is to analyse the knock-on effects on our everyday world and ourselves yielded by this kind of technology. Augmented reality is going to be the most diffused technology in our everyday life in the near future, especially augmented reality mounted on glasses. This near future is not only possible, but it seems inevitable following the vertiginous development of AR. There are numerous kinds of different prototypes that are going to come out next year (2016). Therefore, a study on how these modifications yield knock-on effects on the constitution of the object and subject is mandatory. This work tackles the topic starting from a phenomenological and post-phenomenological point of view and it analyses the modification yielded by such technology from a perceptual point of view using the analysis of the horizons of the object made by Husserl. We need this analysis because it is not only the hypothetical future that may never come, but it is the likely future very close to us that is putting pressure on us.